Level of Knowledge Construction in Elementary School Students: Lesson Plan Analysis - Ummi Nur Laila Sulistyani (Universitas Negeri Malang, 2019)
Abstract: The curriculum should always be updated in line with the changes to keep it relevant to the changing society. The main reason of curriculum changing is as the revision, evaluation, and correction of the previous curriculum. The objective of doing curriculum evaluation is to know whether the currently used curriculum in Indonesia already meet the rubric of 21st CLD and Language Curriculum Design from Nation and Macalister. The research design used in this study was qualitative research. This study applied content analysis approach which focused on senior high school curriculum for English subject. It resulted that 2013 Curriculum used in Indonesia already tried to fulfill the Language Curriculum Design proposed by Nation and Macalister and promote 21st CLS, especially skilled communication. Key Words: curriculum evaluation; language curriculum design; 21st century learning skills; skilled communication Abstrak: Kurikulum harus selalu diperbarui sejalan dengan perubahan agar tetap relevan dengan ma-syarakat yang berubah. Alasan utama perubahan kurikulum adalah sebagai revisi, evaluasi, dan koreksi kurikulum sebelumnya. Tujuan melakukan evaluasi kurikulum adalah untuk mengetahui apakah kurikulum yang saat ini digunakan di Indonesia telah memenuhi rubrik CLD ke-21 dan Desain Kurikulum Bahasa dari Nation and Macalister. Desain penelitian yang digunakan dalam penelitian ini adalah penelitian kualitatif. Penelitian ini menerapkan pendekatan analisis konten yang berfokus pada kurikulum sekolah menengah atas untuk mata pelajaran bahasa Inggris. Hasilnya, Kurikulum 2013 yang digunakan di In-donesia telah dicoba untuk memenuhi Desain Kurikulum Bahasa yang diusulkan oleh Nation and Macalister dan mempromosikan CLS ke-21, khususnya komunikasi yang terampil. Kata kunci: evaluasi kurikulum, desain kurikulum bahasa, keterampilan belajar abad ke-21, komunikasi yang terampil